1999
DOI: 10.1111/0022-4537.00117
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Body Image, and Depressive Symptoms among Low‐Income African American Adolescents

Abstract: The present study tested for gender differences in depression and body image among a sample of 6th-8th grade low-income African American adolescents. Gender differences were found, with adolescent girls more likely to report both depressive symptoms and poor body image. The most frequently endorsed body image concern for both boys and girls was the desire to lose weight, with approximately half of the girls in this sample reporting they would like to lose weight. Results of mediational analyses indicate that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 40 publications
1
31
0
1
Order By: Relevance
“…‡Calculated as follows: (desired weight/reported weight) ϫ 100%. 19), and took diuretics (P = .90). Differences were statistically significant for binge eating (P=.03), fasted (P=.002), smoked more cigarettes (P = .04), and took laxatives (P=.02).…”
Section: Discussionmentioning
confidence: 99%
“…‡Calculated as follows: (desired weight/reported weight) ϫ 100%. 19), and took diuretics (P = .90). Differences were statistically significant for binge eating (P=.03), fasted (P=.002), smoked more cigarettes (P = .04), and took laxatives (P=.02).…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, the majority of work documenting a protective effect with respect to weight among African American females has been comparative in nature (Grant et al, 1999) and the results have drawn attention to potential strengths of this group with respect to weight and body image (Adams, Sargent, Thompson, & Richter, 2000;Cash & Henry, 1995;Cohn et al, 1987;Henriques, Calhoun, & Cann, 1996;Siegel, 2002;Thompson, Rafiroiu, & Sargent, 2003). Given the physical and social consequences of obesity, however, such attitudes are best viewed as a double-edged sword (Beaufort-Lafontant, 2003).…”
Section: Body Size and Weight Concern Among African American Girlsmentioning
confidence: 99%
“…To date, much of the empirical evidence for this association has been based upon comparisons between white youths and youths of color. This research has documented important forms of resilience, but may also have encouraged a simplistic view of African American girls as immune to weight-based distress and thus in need of less support when coping with its effects (Beaufort-Lafontant, 2003;Grant et al, 1999).In this paper we examine the relationship between weight and depression in a cohort of African American girls. In our analysis, we focus first on the psychological consequences of being overweight and experiencing weight gain, specifically as they contribute to depression among a middle school aged cohort.…”
mentioning
confidence: 99%
“…In fact, major depression is the leading cause of disability in 15-44-year-old women (Murray & Lopez, 1996), and the likelihood of experiencing a recurrence of depression increases with each episode (Kovacs, 1997). The sex difference in depression appears to emerge around the time of adolescence (Angold & Rutter, 1992;Ge et al, 1994;Hankin et al, 1998;Petersen, Sarigiani, & Kennedy, 1991), is found within different ethnic groups (e.g., Grant et al, 1999) and with different sampling methods such as community-based (Lewinsohn, Hops, Roberts, Seeley, & Andrews, 1993;Offord et al, 1987;Spence, Najman, Bor, O'Callaghan, & Williams, 2002;Wichstrom, 1999) and high risk samples (Goodyer, Ashby, Altham, Vize, & Cooper, 1993;Grant & Compas, 1995). Initial episodes of depression are also more severe and longer in duration for girls than for boys (McCauley et al, 1993), and girls who experience depression for the first time in childhood or adolescence, compared to women with onsets later in life, have a prolonged period of risk for future episodes (Kovacs, 1997).…”
Section: Sex Differences In Depressionmentioning
confidence: 99%